1998
DOI: 10.4269/ajtmh.1998.58.431
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infections in human immunodeficiency virus (HIV)-positive and HIV-negative individuals in San Pedro Sula, Honduras.

Abstract: Abstract. Honduras has at least five-times more human immunodeficiency virus (HIV)-infected individuals than any other country in Central America. The relationship between HIV status and the presence of intestinal parasites in this part of the world is unknown. This study presents the results from a prospective, comparative study for the presence of parasites in 52 HIV-positive and 48 HIV-negative persons in San Pedro Sula, Honduras. Infection with HIV was determined by microagglutination and confirmed by West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
3
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 20 publications
7
49
3
2
Order By: Relevance
“…In both groups, 33 of the 255 patients (12.9%) were infected with extracellular parasites. This was similar to studies by Lindo et al (1998) and Meamar et al (2007) who reported similar rates in both HIV infected and uninfected individuals studied. HIV-induced enteropathy does not favour the establishment of extracellular parasites (Lindo et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…In both groups, 33 of the 255 patients (12.9%) were infected with extracellular parasites. This was similar to studies by Lindo et al (1998) and Meamar et al (2007) who reported similar rates in both HIV infected and uninfected individuals studied. HIV-induced enteropathy does not favour the establishment of extracellular parasites (Lindo et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…It has been postulated that helminths, such as S. stercoralis, produce different types of intestinal infection in HIVinfected patients, such as chronic diarrhea [6]. This may be due to fact that HIV-induced enteropathy does not favor the establishment of intercellular parasites [7]. Studies made on HIV-positive patients have shown that the morbidity caused by S. stercoralis can be quite debilitating [8,9], and therefore correct diagnosis of this parasite is of great importance.…”
mentioning
confidence: 99%
“…Awole et al 11 also made a similar observation that there is no evidence for an increased prevalence of Giardia lamblia, Entamoeba histolytica in HIV positive patients and exposure to these 2 parasites is likely to occur independently of HIV infection. Lindo et al 12 found that the prevalence of G. lamblia, A.lumbricoides and T. trichura were significantly higher in HIV negative patients. In the present study too, none of the conventional parasites were isolated.…”
Section: Discussionmentioning
confidence: 99%